FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENANGANAN NYERI HAID (DISMENORHEA) PADA SISWI KELAS VII DI MTs. AR-RAHMAH JAKARTA TIMUR - Lulu Mamlukah Rosmayanti (Jurnal Kesehatan Rajawali, 2021)
Management of menstrual pain is a treatment given to treat menstrual pain in adolescent girls. The purpose of this study was to determine the factors in the management of menstrual pain. The design of this study is analytic, with a population of 50 women who have menstruated. This research at MTs. Ar-Rahmah, East Jakarta. With the Total Sampling method. The results of the study more than half (72%) of students at MTs Ar-Rahmah East Jakarta have low knowledge. And more than half (68%) of students at MTs Ar-Rahmah East Jakarta have a negative attitude. More than half (62%) of students at MTs Ar-Rahmah East Jakarta were not exposed to information. More than half (56%) of students at MTs Ar-Rahmah, East Jakarta cannot handle menstrual pain well. Based on the research results, the most important factor in the management of menstrual pain is the knowledge factor.